Analysis on components of characteristic X-ray yield of pure thick targets by positron impact near threshold energy. (30th March 2021) - Ke, Z. X.; Wu, Y.; Pan, M.; Liang, S.; Xu, M. X.; Zhao, Z.; Wang, B. Y.; Zhang, P.
Abstract: In the process of low-energy positron impact with pure thick target, the atomic inner-shell ionization is induced by not only the incident positrons whose energy is completely deposited in the target but also the other particles produced during positron-target collision, namely, the backscattered positrons that deposited part of their energy before escaping the target, the annihilation photons and the secondary electrons. In this paper, the W-M characteristic X-ray yields of two pure thick targets with different diameters impacted by a positron accelerated by the negative high voltage to 5–9 keV have been measured. The contributions from annihilation photons, secondary electrons, backscattered positrons, and the non-uniform electromagnetic field in the target chamber to the characteristic X-ray yields have been evaluated by the realistic Monte Carlo simulation. Besides, Nagashima et al . ( Phys. Rev. Lett., 92 (2004) 223201) neglected the contribution from annihilation photons, secondary electrons and backscattered positrons to the yields when calculating the cross-section by the characteristic X-ray yields of thick target impacted by a positron. Here we also caculated the contribution share of the above particles to the Cu-K and the Ag-L characteristic X-ray yields of pure thick target impact by positrons below 30 keV. The results show that the contributions from the above components are non-negligible. Hence, it is necessary to modify the experimental yields for obtaining the accurate yields of pure thick targets by non-backscattered positron impact.